Functional Requirements in Designing Children’s Toy Stores - Nouri, Osama Ghanim (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed at revealing the functional requirements for designing the interior spaces of children’s toy stores. The research problem can be formulated with the following question: What are the design requirements to take into account when designing children’s toy stores from a functional standpoint? Methodology: The researcher used the descriptive method in analyzing the description and analysis of the research models, as the aforementioned method is characterized by optimal mechanisms to achieve the research objectives, relying thus on collecting information and data related to the research, as the research was determined by studying two samples that were chosen intentionally in the city of Baghdad for both sides of the river (Al-Karkh and Rusafa provinces) for the period limited to 2020-2023. Results: The study showed that the absence of modern and innovative display techniques made children’s toy stores lose their ability to keep pace with the development and technological progress of the era in making the act of shopping successful and looking at what is on display to promote it and saving space. Conclusion: The study concluded that non-employment of modern display techniques does not give shoppers the opportunity to be informed of the largest possible amount of what is on offer and learn more details about it in an interactive manner via (visual display devices) in order to market it without the need to display it inside the space and to save space).